Risk factors associated with the development of dental caries in Bulgarian children - Dobrinka Mitkova Damyanova; Valentina Velikova (International Journal of Public Health Science (IJPHS), 2021)
The purpose of this study was to examine the risk factors associated with the development of dental caries in children in Bulgaria. The research has been carried out at the Faculty of Dental Medicine, in the period 2015-2016, with the permission of the University Scientific Research Committee and informed consent signed by each parent. The subject of observation was parents of children from Varna region in Bulgaria. The results were statistically processed with SPSS v.20.0, using variation and comparison (chi-square) analyzes. For significance level we assume p<0.05. The volume of observation encompasses 100 persons. Units of observation are patients aged three to six years with the need for prevention and treatment of dental caries of the primary dentition. The registration was done in a specially developed questionnaire, including 22 questions, each with the possibility of more than one answer. In processing the obtained data, Student's criterion was used to compare the mean values of two independent samples. In a comparative analysis of the results, we found that 71.01% of children aged three to six years visit a dentist, and patients use fluoride only in the form of toothpaste containing fluoride. When studying the knowledge and behavior of parents in the direction of risk factors for the development of dental caries and oral prophylaxis, need for a new approach of pediatric dentists has been found, focused on programming preventive and non-invasive treatment of children according to their individual needs.